A safety assessment method for substation system dynamics adapted to high penetration of distributed renewable energy sources with backward flow delivery - Xie, Jing dong; Yang, Yuqi; Deng, Huayu; Jiang, Haokun; Hong, Chen; Yan, Lubo (Frontiers in Energy Research, 2025)
The integration of high-penetration distributed renewable energy sources into new power systems introduces significant challenges, particularly frequent reverse power flows that threaten substation security. To address this issue, this paper proposes a novel safety assessment method based on a system dynamics (SD) framework. This approach uniquely emphasizes the critical roles of electrical interconnections among substation equipment and the fluctuations in distributed power output. The methodology involves analyzing operational characteristics to establish equipment correlations, developing a comprehensive fault probability function for each equipment by integrating multi-dimensional monitoring data and fault propagation factors, and constructing a system dynamics model using an adjacency matrix to represent operational relationships. The effectiveness of the proposed method is validated through a case study on a regional substation. Results demonstrate its capability to dynamically and accurately evaluate both equipment-level and system-wide safety status under reverse power flow conditions, providing a robust tool for enhancing the security and resilience of modern power systems.